The widow of Pale Harbor - Fox, Hester (Graydon House, 2019)
Maine, 1846. Gabriel Stone is desperate to escape the ghosts that haunt him in Massachusetts after his wife's death, so he moves to Maine, taking a position as a minister in the remote village of Pale Harbor. But not all is as it seems in the sleepy town. Strange, unsettling things have been happening, and the townspeople claim that only one person can be responsible: Sophronia Carver, a reclusive widow who lives with a spinster maid in the eerie Castle Carver. Sophronia must be a witch, and she almost certainly killed her husband. As the incidents escalate, one thing becomes clear: they are the work of a twisted person inspired by the wildly popular stories of Mr. Edgar Allan Poe. And Gabriel must find answers, or Pale Harbor will suffer a fate worthy of Poe's darkest tales.